Fitness of Paraquat Resistant and Susceptible Biotypes Population of Goosegrass (Eleusine indica (L.) Gaetrn.). Issue 1 (August 2021) - Napitupulu, B S; Purba, E; Mukhlis,
Abstract: A biotype of Paraquat resistant goosegrass ( Eleusine indica (L.) Gaertn.) has envolved in an oil palm plantation in North Sumatera after been treated with Paraquat herbicide in a long period of time. This study aims to investigate the fitness of Paraquat resistant biotype when growing with susceptible biotype in the absence of herbicide. Seeds of Paraquat resistant biotype of Eleusine indica were collected from an oil palm plantation in Deli Serdang and had been proven to have resistant of Paraquat herbicide whereas the susceptible population from a field near campus of Universitas Sumatera Utara which never been exposed to Paraquat herbicide. Both biotypes were planted with proportions of 100 R: 0 S, 75 R: 25 S, 50 R: 50 S, 25 R: 75 S, and 0 R: 100 S with four replications. The result showed that Paraquat resistant biotypes had stronger fitness that the susceptible biotypes.